2016
DOI: 10.2174/0929867323666160425113705
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Phytochemicals in Molecular Target Therapy of Cancer: Potential Inhibitory Effect on Telomerase Activity

Abstract: Telomerase is a ribonucleoprotein enzyme, which has a significant role in synthesizing DNA telomeric in eukaryotes. Telomere maintenance can cause to immortalization and malignant transformation of human cells and thereby telomerase activity must be scrutinized as an important factor in most tumor cells. The proliferation of cancer cells or apoptosis induction can be suppressed by telomerase inhibition using different therapeutic agents without any side effects upon normal cells. Natural substances, with anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Nowadays, numerous natural bioactive compounds or phytochemicals have been isolated, described, and their potential anticancer effects have been evaluated [6][7][8][9]. Although, efficiency of interactions between various dietary compounds needs further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, numerous natural bioactive compounds or phytochemicals have been isolated, described, and their potential anticancer effects have been evaluated [6][7][8][9]. Although, efficiency of interactions between various dietary compounds needs further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown the scavenging potential of a variety of reactive oxygen species including hydroxyl radicals [13]. Cui et al showed that curcumin could suppress telomerase activity and reduce the telomerase expression followed by induction of apoptosis in the cancer cell lines [14]. It has been reported that the induction of apoptosis by curcumin is responsible for such an anti-proliferating effect [15].…”
Section: Introductionmentioning
confidence: 99%
“…The interesting anticancer properties of curcumin has been widely studied in our laboratory (Nasiri et al ., ; Montazeri et al ., ; Mollazade et al ., ; Tabatabaei Mirakabad et al ., ; Kazemiā€Lomedasht et al ., ; Alibakhshi et al ., ; Montazeri et al ., ; Ranjbari et al ., ; Badrzadeh et al ., ; Anganeh et al ., ) and other research groups (Safe and Kasiappan, ; Arumuggam et al ., ). The potential of curcumin to modulate stem cell fate has been reported by several studies.…”
Section: Effects Of Phytochemicals On the Dynamics Of Stem Cellsmentioning
confidence: 98%